Design and Development of Laboratory Scale Updraft Gasifier for Gasification of Oil Palm Fronds - Konda, R.E. (Asian Network for Scientific Information, 2014)
The huge amount of wasted Oil Palm Fronds (OPF) produced annually provides a very good opportunity for the oil palm industry in Malaysia to use it for power generation, especially in mill boilers. Recently, gasification technology is receiving more attention as it can be used to convert wasted biomass into gaseous fuel for power generation and thermal applications as well as it can be used as a fuel source for the production of other chemicals. This study addresses the design, fabrication and performance evaluation of an updraft fixed-bed-gasifier. A 50 kW updraft gasifier is designed and fabricated for gasification of Malaysian oil palm fronds. The gasifier is designed using the empirical data from literature and derived quantities. The gasifier was modified to be very flexible allowing the gasification air to be fed through several locations. The air gasification results of OPF showed volumetric percentage of 22.61-23.36 of CO, 6.48-6.68 of H2, 1.2-1.5 of CH4, 9.51-9.65 of C02 and 59.20-58.1 of N2. The heating value of the product gas mixture varied between 4.1-4.4 MJ Nm"3 while the cold gas efficiency, carbon conversion efficiency and specific gasification rate of the gasifier was in the range of 57-59 and 95-97 and 103-109 kg m~2 h-1, respectively. The study has demonstrated that the oil palm frond waste is suitable for the designed and fabricated updraft gasifier and the produced gas from the gasification of OPF was successfully used in a domestic cooking stove. Â© 2014 Asian Network for Scientific Information.